2007
DOI: 10.1177/1350508407080313
|View full text |Cite
|
Sign up to set email alerts
|

Legal Professionals and Transnational Law-Making: A Case of Distributed Agency

Abstract: Abstract. In institutional theory, it is a challenge to explain how rulesetting occurs in transnational contexts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 68 publications
0
93
1
2
Order By: Relevance
“…Moreover, legal experts often mobilize their expertise to be actively engaged in policy enterprises, even transnationally. Previous studies have shown that the active engagement of legal experts has directly contributed to the global harmonization of contract law (Braithwaite and Drahos 2000), administrative law (Jordana and Levi-Faur 2005), competition law (Waarden and Drahos 2002), corporate law (Quack 2007), and litigation procedures (Kelemen and Sibbit 2004). The role of legal experts in the European integration process (Burley and Mattli 1993;Newman 2008) and in the Americanization of some Latin American countries has been especially well documented (Gardner 1980;Dezalay and Garth 2002;Mattei 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Moreover, legal experts often mobilize their expertise to be actively engaged in policy enterprises, even transnationally. Previous studies have shown that the active engagement of legal experts has directly contributed to the global harmonization of contract law (Braithwaite and Drahos 2000), administrative law (Jordana and Levi-Faur 2005), competition law (Waarden and Drahos 2002), corporate law (Quack 2007), and litigation procedures (Kelemen and Sibbit 2004). The role of legal experts in the European integration process (Burley and Mattli 1993;Newman 2008) and in the Americanization of some Latin American countries has been especially well documented (Gardner 1980;Dezalay and Garth 2002;Mattei 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In line with the approach taken in North America and Western Europe, many firms have sought to enter markets not to work on domestic matters, but to establish their role in the local legs of global deals (Faulconbridge and Muzio, 2015;Quack, 2007). Of course, the distinction between domestic and global deals is not clear cut.…”
Section: Entering and Shaping Emerging Marketsmentioning
confidence: 99%
“…They are particularly important because of their central role in choreographing the global economy and setting the rules of the game for capitalist activities (Quack, 2007). In this chapter, we consider their work, both in terms of their activities and internal organization as 'global' firms and in terms of their impacts on economies and ultimately societies worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on the role of professional environments and experts in global governance has focused on areas such as accountancy governance (Botzem, 2008;, banking regulation (Lall, 2012;Young, 2012), financial reform (Baker, 2010;Seabrooke & Tsingou, 2014) and transnational lawmaking (Trubek et al 1994;Quack, 2007). This paper builds on these works but also complements them in important ways, empirically and theoretically.…”
Section: Introductionmentioning
confidence: 99%